This I Believe - Draper, Mary C. (Tufts Archival Research Center, 2006)
Mary Draper, a meber on the boards of Brooklyn Bureau of Social Service, Children's Aid Society, and Long Island University Hospital, describes her belief in equality and change as a positive force in the world and peoples lives, positive change she has seen in people through her work and she hopes for changes in the world that will bring peace and progress.